A metal goal of the University of the Philippines system a recommendation - Martires, Concepcion R. (Education quarterly.)
The University of the Philippine should start with the person of the student which is its raison d'etre. The U.P. graduate who is also humanly developed is a greater asset than the one who is only academically and professionally prepared.Even in the midst of the futuristic asphalt jungle, this human individual is able to relate humanely to others after having been made perceptive and responsible to himself and others and effective with himself and others. He is one of the good contributions of the University to the achievement of the development goals of the country.